The effect of isolated probiotics from Indonesian Passiflora edulis sims. on interferon gamma levels in peripheral blood mononuclear cell of adult tuberculosis patients in vitro - Iif H. Nurrosyidah; Ni M. Mertaniasih; Isnaeni Isnaeni (AOSIS, 2023)
Background: Mycobacterium tuberculosis (M.tb) is unique because the bacteria live intracellularly and hide in macrophages so that they can escape from phagocytosis. This is one of the factors that complicate the treatment of M.tb infections. Interferon-gamma (IFN-γ) is a compound that plays an important role in macrophage activation to control intracellular pathogens. Objective: The purpose of this research is to analyze the concentration of IFN-γ in peripheral blood mononuclear cells of adult Tuberculosis patients (TB) after in vitro administration of multistrain probiotics from indigeneous Indonesian red passion fruit (Passiflora edulis Sims.). Method: The probiotics isolated from red passion fruit were introduced into Peripheral Blood Mononuclear Cell (PBMC) adult TB patients who were undergoing Anti-tuberculosis Drug Therapy (ATD) category one at the Trosobo Primary Health Center (Sidoarjo, East Java, Indonesia), and the patients who were undergoing ATD category one treatment were willing to be involved in this study. Result: The probiotics isolated from fermentation-broth of Indonesian red passion fruit were able to increase IFN-γ levels in PBMC of adult TB patients. Conclusion: The red passion fruit probiotics isolated can increase IFN-γ of adult TB patients increased from 0.82% to 23.17% after in vitro administration.